Bladder cancer subtypes exhibit limited plasticity across different microenvironments and in metastases - Carina Bernardo; Subhayan Chattopadhyay; Natalie Andersson; Pontus Eriksson; Benjamin Medle; Lena Tran; Nour al dain Marzouka; Adam Mattsson; Aymeric Zadoroznyj; Malin Larsson; Fredrik Liedberg; Mattias Höglund; et al. (Experimental Hematology & Oncology)
Abstract Background Transcriptomic and genomic analyses of bladder cancer (BC) reveal a highly diverse disease stratified into molecular subtypes with distinct molecular features and biological behaviors. Intratumor heterogeneity (ITH) and plasticity can significantly impact diagnosis and patient management, yet their extent in BC remains highly debated. Here, we investigated whether the three main bladder cancer subtypes maintain or alter their identity in response to changes in the microenvironment and during metastatic colonization. Methods Seven patient-derived xenograft (PDX) models representing the major BC subtypes were propagated into three distinct tissue microenvironments: subcutaneous, mammary fat pad and under the kidney capsule. Metastatic lesions were generated via systemic injection of tumor cells. Tumor samples were analysed using RNA- and exome sequencing, SNP-arrays and histopathology to assess subtype fidelity, genomic evolution, and clonal dynamics. Results A comprehensive, longitudinal multiomics analysis showed that tumors consistently maintain their molecular subtype, as well as their transcriptomic and genomic profiles, across different environments. No evidence of emerging ITH or subtype transitions was observed, regardless of the microenvironment. The transcriptomic adaptations observed in metastases and different implantation sites are limited and are associated primarily with hypoxia, epithelial-mesenchymal transition (EMT), and invasion. Conclusions Our results suggest that invasive bladder cancers have a strong intrinsic tumor identity that is not easily reprogrammed by the microenvironment.